Perancangan Sistem Informasi Arsip Surat pada Kantor Hukum Kofipindo - Milawati, Milawati; Alisya Alfina Rizki Ritonga; Aidil Halim Lubis (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to design and build a letter archive information system at the KOFIPINDO Law Office to improve the effectiveness and efficiency of document management. The manual filing system that has been used so far poses various obstacles, such as search delays, the risk of losing documents, and low storage accuracy. To overcome these problems, this study applies the Waterfall System Development Life Cycle (SDLC) model in the process of designing and building the system. Web-based technologies used include PHP, HTML, CSS, Bootstrap, and MySQL. The results of the study show that the developed letter archive information system is able to simplify the process of storing, searching, and managing incoming and outgoing letters in a faster, structured, and safer manner. The implementation of this system not only improves administrative performance, but also strengthens accountability and supports the need for professional legal documentation within the KOFIPINDO Law Office. Thus, this web-based mail archive information system can be a strategic solution in modernizing legal document management.